Community Service Based on Senam Anak Indonesia Hebat to Improve Health and Cheerfulness of Students at SD Negeri 104230 Batang Kuis - Fine Siska Wati Waruwu; Forman Juniar Doloksaribu; Fikram Daya; Wisda Syahputra; Fitri Sari Pandingan (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2026)
Objectives: The decline in physical activity in elementary school children due to the influence of technology and a sedentary lifestyle has an impact on students' health and learning concentration (Mahmud & Rahman, 2024). SD Negeri 104230 Batang Kuis requires movement-based interventions to improve students' fitness and enthusiasm for learning. This community service activity aims to improve the physical health, cheerfulness, and mental readiness to learn of students of SD Negeri 104230 Batang Kuis through the implementation of the Great Indonesian Children's Gymnastics (SAIH) program. Methods: The activity was implemented using a participatory approach through stages of socialization, teacher training, movement demonstrations, and routine implementation assistance for 8 weeks (Sugiyanto & Putri, 2024). Evaluation was carried out through participatory observation, measuring physical responses (heart rate), and assessing student learning concentration. Results: The program showed a significant increase in student participation (96.5%), a decrease in heart rate from 98.3 to 86.7 bpm, and an increase in concentration scores from 62.4 to 78.6 (Mahmud & Rahman, 2024). The majority of students (96.5%) showed a high interest in exercising and better mental readiness to learn (Prasetyo & Wulandari, 2024). Conclusion: This activity successfully built healthy lifestyle habits, improved students' physical fitness, and strengthened character values such as discipline, hard work, and sportsmanship (Kurniawan & Susanti, 2024). Partner schools integrated SAIH as a routine program in school activities.